2016
DOI: 10.1038/nclimate3114
|View full text |Cite
|
Sign up to set email alerts
|

The increasing importance of atmospheric demand for ecosystem water and carbon fluxes

Abstract: Soil moisture supply and atmospheric demand for water independently limit-and profoundly a ect-vegetation productivity and water use during periods of hydrologic stress [1][2][3][4] . Disentangling the impact of these two drivers on ecosystem carbon and water cycling is di cult because they are often correlated, and experimental tools for manipulating atmospheric demand in the field are lacking. Consequently, the role of atmospheric demand is often not adequately factored into experiments or represented in mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
822
5

Year Published

2017
2017
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 942 publications
(935 citation statements)
references
References 28 publications
41
822
5
Order By: Relevance
“…Sumner and Jacobs, 2005;Granier et al, 2000;Jones, 1992;Novick et al, 2016) has been well studied and incorporated in most conventional stomatal or canopy conductance models (e.g. 5 Leuning, 1995;Jarvis, 1976;Ball et al, 1987).…”
Section: Performance Of the Penman-monteith Methodsmentioning
confidence: 99%
“…Sumner and Jacobs, 2005;Granier et al, 2000;Jones, 1992;Novick et al, 2016) has been well studied and incorporated in most conventional stomatal or canopy conductance models (e.g. 5 Leuning, 1995;Jarvis, 1976;Ball et al, 1987).…”
Section: Performance Of the Penman-monteith Methodsmentioning
confidence: 99%
“…Most existing studies on water vapor focus on analyzing the surface relative humidity (Simmons et al, 2010;Vincent et al, 2007;. However, Novick et al (2016) proposed that atmospheric demand for water was 390 directly related to the vapor pressure deficit (VPD) which also affected the surface conductance to water vapor and ET. In our study, we found sharply increased VPD after 1987, which has caused the increased ETo over QRB.…”
Section: Implication Of Increasing Vpd and Eto For Future Agriculturamentioning
confidence: 99%
“…The photosynthesis module in OR-CHIDEE largely follows Yin and Struik (2009), in which stomata conductance decreases with an increasing VPD, and thus is able to simulate a lower GPP under dry air conditions. A recent study (Novick et al, 2016) showed that, between the two factors that impact plant water stress, i.e., soil moisture supply and atmospheric demand for water (reflected by VPD), the latter limits evapotranspiration to a greater extent than the former in relatively wet forested ecosystems. In spite of its importance, the effect of VPD on vegetation productivity has been far less studied than soil water availability (Konings et al, 2017), warranting further investigations in both observations and land surface models.…”
Section: Leaf Area Indexmentioning
confidence: 99%